Exploring the Effects of Various Two-Dimensional Supporting Materials on the Water Electrolysis of Co-Mo Sulfide/Oxide Heterostructure - Ngoc-Diem Huynh; Won Mook Choi; Seung Hyun Hur (Nanomaterials, 2023)
In this study, various two-dimensional (2D) materials were used as supporting materials for the bimetallic Co and Mo sulfide/oxide (CMSO) heterostructure. The water electrolysis activity of CMSO supported on reduced graphene oxide (rGO), graphite carbon nitride (gC3N4), and siloxene (SiSh) was better than that of pristine CMSO. In particular, rGO-supported CMSO (CMSO@rGO) exhibited a large surface area and a low interface charge-transfer resistance, leading to a low overpotential and a Tafel slope of 259 mV (10 mA/cm2) and 85 mV/dec, respectively, with excellent long-term stability over 40 h of continuous operation in the oxygen evolution reaction.